KOMITMEN ORGANISASI SEBAGAI PEMODERASI PENGARUH GOOD GOVERNANCE DAN KOMPETENSI AUDITOR PADA KUALITAS AUDIT (Studi Empiris Pada Kantor Badan Pengawasan Keuangan dan Pembangunan Provinsi Papua) - Prihatining Tyas Dwi; Meinarni Asnawi; Bill J.C Pangayow (Jurnal Akuntansi dan Keuangan Daerah, 2017)
The purpose of this study is to analyze the influence of good governance and auditor competence on audit quality with organizational commitment as the moderating variable. The number of samples taken are 33 auditors, because of the lack of difficulty in obtaining the questionnaires. This study used purposive sampling method by distributing questionnaires to respondents with criteria of junior auditor and senior auditor, and then collected directly from them. Afterwards, the collected data was processed by direct distribution method. Analytical technique used in this study was WarpPLS (Partial Least Square) version 5.0. The results of this study indicate that good governance has a significant effect on audit quality; while auditor competence has no significant effect on audit quality; where organizational commitment does not moderate the relationship of good governance and audit quality; also organizational commitment does not moderate the relationship between auditor competence and audit quality.